Effects of compressed work schedules on sickness absence - Elisabeth Fevang; Andreas Fidjeland; Karen Hauge; Otto Sevaldson Lillebø (University of Oslo, Department of Economics, 2024)
Steadily increasing demand for personnel has led health care providers to seek more efficient uses of the healthcare workforce. One potential solution is to find ways of organizing work schedules that are more attractive and sustainable for workers. The primary objective of this article is to investigate how compressed work schedules (CWS), a scheduling practice with fewer but longer shifts, affects sickness absence. We do so by leveraging a nation-wide retrospective survey mapping the use and changes between different work schedules in the Norwegian municipal health and care sector, coupled with precise employee-level registry data, to conduct a quasi-experimental analysis of the impact of introducing CWS at the workplace on employees. Our preferred empirical approach involves leveraging observations of employees at workplaces that introduce CWS and workplaces that do not, in a differences-in-differences design. We find no significant effects on sickness absence. The results are robust to different definition of sickness absence.
Keywords: I10; J22; J28; J45; J81; 330; Healthcare workers; health and care services; shiftwork; sickness absence